The Relationship Between Second Language Anxiety and International Nursing Students Stress - Khawaj, Nigar G; Chan, Sabrina; Stein, Georgia (Journal of International Students, 2018)
We examined the relationship between second language anxiety and international nursing student stress after taking into account the demographic, cognitive, and acculturative factors. International nursing students (N=152) completed an online questionnaire battery. Hierarchical regression analysis revealed that spoken second language anxiety and the acculturative factors of marginalization and separation were significantly related to academic-related and placement-related stress in international nursing students. The results suggest that international nursing students, along with the pressures of their course, encounter second language anxiety particularly with reference to its spoken aspect. Subsequently, interventions aimed at building resilience in international nursing students should include coping and management of second language issues.